Aggregation‐Induced Dual‐Phosphorescence from Organic Molecules for Nondoped Light‐Emitting Diodes. Issue 51 (6th November 2019) - Wang, Tao; Su, Xiaoge; Zhang, Xuepeng; Nie, Xiancheng; Huang, Linkun; Zhang, Xingyuan; Sun, Xiang; Luo, Yi; Zhang, Guoqing
Abstract: Aggregation‐induced emission (AIE) is a beneficial strategy for generating highly effective solid‐state molecular luminescence without suffering losses in quantum yield. However, the majority of reported AIE‐active molecules exhibit only strong fluorescence, which is not ideal for electrical excitation in organic light‐emitting diodes (OLEDs). By introducing various substituent groups onto the biscarbazole compound, a series of molecular materials with aggregation‐induced phosphorescence (AIP) is designed, which exhibits two distinctly different phosphorescence bands and an absolute solid‐state room‐temperature phosphorescence quantum yield up to 64%. Taking advantage of the AIE feature, the AIP molecules are fabricated into OLEDs as a homogeneous light‐emitting layer, which allows for relatively small efficiency roll‐off and shows an external electroluminescence quantum yield of up to 5.8%, more than the theoretical limit for purely fluorescent OLED devices. The design showcases a promising strategy for the production of cost‐effective and highly efficient OLED technology. Abstract : Combining the advantages of aggregation‐induced emission (AIE) and organic room‐temperature phosphorescence (RTP), as‐designed RTP‐AIEgens show a maximum photoluminescence quantum yield of 64%. Devices are then fabricated, and nondoped organic light‐emitting diodes (OLEDs) based on the RTP AIEgens exhibit relatively small efficiency roll‐off and efficient electroluminescence quantum efficiency, breaking the theoretical limit of conventional fluorescent OLEDs.